Design and Implementation of a Low-Cost Aircraft Orientation Angle Measurement System using MPU6050 Sensor for Avionics Education - Jamil, Ramadani; Kurniawan, Freddy; Irawaty, Mardiana; Lasmadi, Lasmadi; Funny, Rindu Alriavindra (Vortex, 2025)
This study presents the design and implementation of a low-cost aircraft orientation angle measurement system using the MPU6050 sensor and Arduino Uno microcontroller for educational applications in avionics. The system aims to simulate aircraft attitude angles—yaw, pitch, and roll—by integrating an inertial sensor module (MPU6050) with open-source hardware and software. The Arduino IDE was employed to acquire and process sensor data, while the Processing 3 environment was used to visualize the attitude motion in real time. The prototype was assembled and tested to evaluate its performance in detecting orientation changes across three axes. Experimental results demonstrate that the MPU6050-based system can accurately capture and display attitude variations without communication delay or signal error, providing a clear visualization of aircraft motion. The system’s simplicity, affordability, and open-source framework make it suitable for classroom demonstrations and laboratory exercises in avionics and control-system courses. Future improvements include the integration of Euler-angle computation and wireless communication to enhance mobility and data acquisition.